2017
DOI: 10.4067/s0718-221x2017005000101
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of sanding parameters using response surface methodology

Abstract: The main objective of this work is to develop a mathematical model to evaluate optimum sanding conditions of Europen black pine (Pinus nigra). Samples were sanded using different of grit size, feed rate, cutting speed and depth of cut. Average surface roughness (R a ) values of each type of specimens were measured employing a stylus type of equipment. Interaction between sanding parameters and surface roughness of the species were analyzed using Minitab software and response surface methodology. Based on the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…was very smooth when Belleville et al (2016) used higher grit sized sand papers. Hazir et al (2017) cites the report of Varanda et al (2010) which reveals that smaller abrasive grains resulted in higher surface roughness of the samples of Eucalyptus grandis. Roughness parameters of samples sanded with 180 grit were lower in contrast to samples planned or sanded with 60 grit (Relaño et al 2017).The occurrence of torn grains in M. dubia during sanding may thus be mostly attributed to the tearing of fibres and use of relatively smaller grits used in the test.…”
Section: Resultsmentioning
confidence: 52%
“…was very smooth when Belleville et al (2016) used higher grit sized sand papers. Hazir et al (2017) cites the report of Varanda et al (2010) which reveals that smaller abrasive grains resulted in higher surface roughness of the samples of Eucalyptus grandis. Roughness parameters of samples sanded with 180 grit were lower in contrast to samples planned or sanded with 60 grit (Relaño et al 2017).The occurrence of torn grains in M. dubia during sanding may thus be mostly attributed to the tearing of fibres and use of relatively smaller grits used in the test.…”
Section: Resultsmentioning
confidence: 52%
“…They found that the roughness and machining forces largely increased with increased feed rate but slightly decreased with increased spindle speed. In another study, Hazir et al 87 measured the roughness and established a model to optimize depth of cut, grit size, cutting speed, and feed rate for sanding European black pine. Reprinted by permission from Elsevier: Measurement.…”
Section: Surface Roughness Of Wood Materialsmentioning
confidence: 99%
“…Modification of wood and wood-based materials with air plasma treatment can reduce or eliminate these negative properties of wood material. This process is widely used to improve the wettability, fluid uptake, or adhesion properties of wood [ 33 , 34 , 35 ]. In several studies, it has been concluded that plasma treatment mainly increases the polar component of the surface energy and positively affects the wood surface properties [ 36 , 37 , 38 , 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%